Atmospheric Propagation 2003
DOI: 10.1117/12.473178
|View full text |Cite
|
Sign up to set email alerts
|

Phase diffuser at the transmitter for lasercom link: effect of partially coherent beam on the bit-error rate

Abstract: By using a complex phase screen model for a diffuser located at the transmitter, analytic expressions are developed for the scintillation index of a lowest order Gaussian-beam wave in the pupil plane of the receiver in weak and strong atmospheric conditions. The effect of partial coherence on the scintillation index is analyzed as a function of the propagation distance and the correlation length of the diffuser. The reduction in the scintillation level (due to the transmitter aperture averaging effect) is show… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…The quantity x in Eq. ͑40͒ is the normalized large-scale cutoff frequency determined by the asymptotic behavior of ln x 2 in weak turbulence and saturation regime 36,38 :…”
Section: ͑40͒mentioning
confidence: 99%
“…The quantity x in Eq. ͑40͒ is the normalized large-scale cutoff frequency determined by the asymptotic behavior of ln x 2 in weak turbulence and saturation regime 36,38 :…”
Section: ͑40͒mentioning
confidence: 99%
“…The spatial diffuser placed over the laser exit is modeled as a thin complex phase screen with a Gaussian spectrum model [5][6][7] ( ) where κ (m -1 ) is the atmospheric wave number, l c (m) is the lateral correlation radius of the Gaussian phase screen. In model (2.2), <n 1 2 > is the fluctuation in the index of refraction induced by the screen.…”
Section: Basic Modelmentioning
confidence: 99%
“…Although simply physically realizable Free-Space Laser Communication and Active Laser Illumination III, edited by David G. Voelz, Jennifer C. Ricklin (usually with the help of a commercially sold diffuser placed over the laser exit) the new approach requires the development of a theoretical model for partially coherent beams propagating in atmospheric turbulence that could be useful for the FSO system design. Usually in literature existing on this account [10][11][12][13][14][15][16][17][18] one can find the analytic results only for two limiting cases of fast and slow detection and only for one of the atmospheric conditions: weak fluctuations or saturation regime. A model valid in all atmospheric fluctuations (weak-moderate-strong) was suggested by the authors for the particular case of a slow detector [5][6][7] where it was demonstrated that the application of the diffuser can significantly improve the FSO system performance. The purpose of this paper is to extend previous results to the case of arbitrary detection speed.…”
Section: Introductionmentioning
confidence: 99%
“…Although conceptually this idea seems to be similar to our proposal, the motivation in [37,38] is to reduce the scintillation at the entrance pupil of the coupler. As it is clear from our analysis, phase disturbances play the dominant role for the PIF fluctuations.…”
Section: Adaptive Optics and Fadingmentioning
confidence: 72%
“…Papers [37,38] considered the mitigation of the PIF scintillation by using the partially-coherent sources, or equivalently a diffuser place at the transmitter plane L z = in our notations. Although conceptually this idea seems to be similar to our proposal, the motivation in [37,38] is to reduce the scintillation at the entrance pupil of the coupler.…”
Section: Adaptive Optics and Fadingmentioning
confidence: 99%